A COMPARISON OF DIFFERENT LIPOPOLYSACCHARIDE CHEMOTYPES FROM ESCHERICHIA COLI AND SALMONELLA UPON SYNTHESIS OF TNFα AND IL-6 BY MACROPHAGE-LIKE THP-1 CELLS - E. V. Voloshina; S. V. Zubova; S. V. Prokhorenko; N. I. Kosjakova; I. R. Prokhorenko (Медицинская иммунология)
Abstract. Present study was performed to investigate the influence of polysaccharide fragment or lipid A upon induction of TNFα and IL-6 cytokines. The study was performed with human THP-1 monocytic leukemia cells that were induced to differentiate into macrophage-like cells using PMA treatment. Bacterial lipopolysaccharides from S. typhimurium (S-chemotype form), S. typhimurium SL1181 (R-chemotype, Re-mutant), E. coli O55:B5 (S-chemotype), and E. coli JM103 (R-chemotype, Re-mutant) were used in this study. A decreased molar ratio for lipid A-KDO in S-form of LPS from E. coli is accompanied by diminished TNFα and IL-6 expression. By the contrast, for S-form of LPS from Salmonella, a decrease in lipid A-KDO molar ratio did cause a sufficient enhancement of TNFα expression. A contribution of lipid A structure into biological activity of LPS is more significant for Re-chemotype than for S-chemotype, independently on bacterial species.